Consulting report – Llama Pack project - Chiles, Natalia Michele; Lora Prado, Gonzalo Andre; Martini, Iris Felicia; Scheuer, Tobias; Singh, Gurman (Pontificia Universidad Católica del Perú, 2023)
The following report is the result of a consulting project carried out by five Master of Global Business students in the Consulting Methods and Practice course of Centrum PUCP in collaboration with the Llama Pack Project (LPP). The main challenge of the LPP could be identified as the ambition to grow its educational tourism through capitalizing from the resources they already have. Through an industry analysis (chapter 1.1), a SWOT analysis (chapter 1.3 and 1.4) and with the help of a literature review (chapter III) including a thorough analysis (chapter IV), the environment which LPP is operating in could be identified. The quantitative analysis determines the US market as the most potential one with around 35,000 US students visiting for educational tourism the region LPP is operating. There are three main reasons why LPP could not yet tackle the challenge by its own: time constraint, lack in work task structuring and the complexity of their interest to grow (chapter V). Based on the results of the single analysis, five potential solutions could be identified. With the help of weighted criteria of feasibility, acceptability, financial cost, suitability, and strategic alignment, these five alternatives were assessed (chapter VI). The evaluated and final proposed solution consists of multi-steps and suggests LPP to collaborate with existing contacts from past networking events, work more with US based student travel agencies and finally directly communicate to US universities for educational program opportunities (chapter VII). To incorporate these alternatives in LPP’s business activities a three-phase implementation plan including a Gantt Chart and a practical implementation plan have been developed (chapter VIII). The elaboration consists of specific marketing activities, preparation guides for networking and budgets. The most relevant outcomes for LPP will be a 100% increase in booked student groups by December 2024 which includes 66% more partners in travel agencies and 3 new university partners (chapter IX).
Keywords: Consultores de empresas--Planificación estratégica; Turismo--Administración--Perú; Ambiente educativo; Desarrollo económico--Perú; https://purl.org/pe-repo/ocde/ford#5.02.04